Cyberstalking sebagai Kejahatan Multidimensional - Ketut Ratri Wahyuningsih (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The rapid development of information technology has brought various conveniences to human life, but it also brings new challenges in the form of cybercrime threats. One of these threats is cyberstalking, which is the act of stalking, harassment, or threats through digital media. Cyberstalking utilizes the anonymity of technology to violate the privacy, dignity, and psychological safety of the victim. In Indonesia, the regulation of cyberstalking is implicitly regulated through Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) or in its latest amendment, namely in Law Number 1 of 2024 concerning the Second Amendment to Law Number 1 of 2008 concerning Electronic Information and Transactions and the Criminal Code (KUHP). However, these regulations have not been able to cover the multidimensional dimensions of the crime, such as non-verbal harassment or emotional threats through digital media. This article analyzes cyberstalking in the perspective of Indonesian criminal law by highlighting the existing legal vacuum and the importance of regulatory reform based on the principles of legality, legal certainty, and protection of individual rights. Recommendations include revising the ITE Law, strengthening the capacity of law enforcers, and increasing public awareness to deal holistically with the threat of cyberstalking. With these steps, it is hoped that legal protection for victims can be improved in line with technological developments.